Silent Effects of High Salt: Risks Beyond Hypertension and Body’s Adaptation to High Salt - Raisa Nazir Ahmed Kazi (Biomedicines)
Hypertension is a major contributor to heart disease, renal failure, and stroke. High salt is one of the significant risk factors associated with the onset and persistence of hypertension. Experimental and observational studies have confirmed cardiovascular and non-cardiovascular detrimental effects associated with chronic intake of high salt. Because of convenience and present urban lifestyles, consumption of fast food has led to daily salt intake above the recommended level by the World Health Organization. This study provides an understanding of the body regulatory mechanisms that maintain sodium homeostasis under conditions of high salt intake, without health consequences, and how these mechanisms adapt to chronic high salt load, leading to adverse cardiovascular, renal, and non-cardiovascular outcomes. Recent research has identified several mechanisms through which high sodium intake contributes to hypertension. Of them, heightened renin–angiotensin–aldosterone and sympathetic activity associated with impaired pressure diuresis and natriuresis and decreased renal excretory response are reported. Additionally, there is the possibility of endothelial and nitric oxide dysfunction leading to vascular remodeling. These changes raise cardiac output and peripheral vascular resistance. Knowing how these collective mechanisms adapt to chronic intakes of high salt helps develop effective therapeutic policies to fight salt-induced hypertension.